Demonstrating competence in Endoscopic Retrograde Cholangiopancreaticography (ERCP): recently credentialed operator’s performance for deep biliary cannulation over 1 year period from tertiary care hospital in Pakistan - Om Parkash; Umar Bhatti; Hasnain Zafar; Saeed Hamid (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To measure the success rate of endoscopic retrograde cholangiopancreaticography biliary cannulation of a recently credentialed endoscopist at a tertiary hospital. Methods: The clinical audit was conducted at the Aga Khan University Hospital. Karachi, and comprised data of all patients who underwent endoscopic retrograde cholangiopancreaticography under the care of a single operator during 2016. Data was retrospectively extracted from patient charts by an assistant blinded to the study. Data extracted included demographics, admission type, details and indication for the procedure, diagnosis, cannulation outcome, duct clearance, complications, follow-up surgical intervention, radiological imaging and mortality post-endoscopy. Data was analysed using SPSS 19. Results: Of 143 procedures performed, 102(71.3%) were included. The mean age was 52±17 years and 54(52.9%) of them were females. Most common indication was choledocholithiasis in 70(68.6%). The average procedure time was 41.5±5.5 minutes. Cannulation success rate was 96(94.1%). Complications included post-procedure pancreatitis in 5(4.9%), minimal bleeding in 8(7.8%) and oesophageal perforation in 1(0.98%). There was no procedure-related mortality. Conclusion: The success rate was high and complications were low Continuous...